Integral recovery of an urban watershed through the implementation of nature-based solutions - Bonilla Brenes, Ricardo; Hack, Jochen; Morales, Martín; Oreamuno, Rafael (Frontiers in Sustainability, 2024)
Unplanned urban expansion in Latin America has profoundly disturbed the natural hydrological processes of watersheds, particularly in tropical regions with extreme weather conditions. This has resulted in substantial runoff volumes, necessitating extensive engineering interventions to avoid damage. Urbanization has led not only to flooding problems, but also to a lack of recreational spaces for residents and an ecological degradation, negatively affecting the watersheds health.This study shows a methodology for creating scenarios making use of available sites for Naturebased-Solutions (NbS). Taking account of existing land cover, the methodology harnesses NbS multifunctionality to achieve hydrological, ecological and social benefits counteracting the threats to the health of a 23 km 2 urban tropical watershed located in Costa Rica. In these scenarios, suitable public roads in residential areas were used as sites for implementing permeable pavement, bioretention cells, infiltration trenches and street planters, while appropriate flat roofs and car parks were converted into green roofs and permeable pavements in industrial areas. In addition, several green public spaces were transformed into multifunctional storage areas. Hydrological and hydraulic modelling was used to evaluate the performance of each scenario, while the increase in green area of each scenario was used as an indicator of the ecological and social benefits. The concurrent implementation of the residential, industrial and green space scenarios provides an area available for NbS of 165.3 ha (7.2% of the watershed area), potentially leading to a decrease of up to 63.7% in peak flow and up to 46.2% in runoff volume for a specific rainfall event.As haphazard urban growth is a common feature of most urban watersheds in Latin America, this methodology, based on the use of different land cover types to create scenarios for NbS implementation, is transferable to and adaptable for other tropical urban watersheds.